The Dynamics of International Trade, Capital Flow, and Economic Growth in Developing Economies - Rana Shahid Imdad Akash; Majid Imdad Khan; Falik Shear (Journal of Management Practices, Humanities and Social Sciences, 2023)
This research aimed to explore the dynamics of international trade, capital flows and Gross domestic product developing economies from January 1, 2013 to Dec 31, 2022. Bivariate and Multivariate Cointegration, Granger Causality, and Vector Error Correction Model (VECM) tests were considered for results calculation. The methodology explored the short/long run and cause and effect relation among variables. International trade and Capital flow integrated financially with international investment of GDP. GDP was showing the growth of investment with capital flow to provide more opportunities for investors. Capital flow and international trade regarding cointegration effect, GDP exposed the relation with these. The Bivariate Co integration of GDP with capital flow and international trade exist. A short run dynamic of capital flow with GDP and GDP with International trade exists. It is implicated that return’s behavior regarding investment could be a best for economic upswing and to choose the policies about macroeconomics, financial markets and to choose the best flight for assisting escalation investment process growth, portfolio investment during financial globalization. Moreover, business culture improvements will attract government to regard the multinational and national investors in case of early competition, and economic growth long run.